SCIENTIFIC FOUNDATIONS AND EFFECTIVENESS OF CONDUCTING PHYSICAL EDUCATION LESSONS IN HIGH-TEMPERATURE CONDITIONS IN RURAL SCHOOLS (Scientific journal of the Fergana State University, 2025)
This study analyzes the importance of developed methods for effectively conducting physical education lessons in rural schools under high-temperature conditions. A pedagogical experiment examined the impact of static gymnastics and breathing exercises on students' physical fitness. The results demonstrated improved mobility and physical strength during the exercises.